EFEKTIVITAS PENDIDIKAN KESEHATAN TENTANG TERAPI PIJAT REFLEKSI APIYU (ALAT PIJAT KAYU) PADA PASIEN DIABETES MELITUS TIPE 2 - Gustia " Marliyuna; Yesi " Hasneli; Juniar " Ernawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract   The purpose of this study is to identified the effectivity of health education about APIYU reflexology massage therapy to Diabetes Mellitus type 2 patient. The research used pre-eksperimental design without control group. Participants of this study were 34 people. Samples taken using non probability sampling technique.  Data collection used in this study was a questionnaire about APIYU reflexology massage.  The participants group were given health education about APIYU reflexology massage. Data analyzed using Wilcoxon test. The results of the study  shows that level of knowledge before intervention is  8.50 with maximal and minimal value 5 and 14 and after is 14.0 with maximal and minimal value 7 and 15 (p value = 0.000), It mean that there is an increase knowledge after received information about APIYU. The results of this study recommen that health education about APIYU reflexology massage can increase  patient’s knowledge about APIYU reflexology massage. The finding of this study can be used  of nursing intervention to increase patient’s knowledge about APIYU reflexology massage for Diabetes Mellitus Type 2. Keywords: APIYU reflexology massage, Diabetes Mellitus Type 2, Health education.